2012
DOI: 10.1007/s11038-011-9385-4
|View full text |Cite
|
Sign up to set email alerts
|

Lavras do Sul: A New Equilibrated Ordinary L5 Chondrite from Rio Grande do Sul, Brazil

Abstract: The new Brazilian chondrite, Lavras do Sul was found in 1985 at Lavras do Sul, Rio Grande do Sul State. Brazil. (33°30'48"S; 53°54'65"W). It consists of one mass weighting about 1kg and being covered by a black fusion crust with grayish interior. Four polished thin sections were prepared from a slice weighing 67g on deposit at Museu Nacional/UFRJ. It consists mostly of chondrules and chondrule fragments dispersed in a recrystallized matrix. Most chondrules are poorly defined and range in size from 300µm to 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the studies of equilibrated L ordinary chondrites Villalbeto de la Peña L6 and Lavras do Sul L5 [88,89], the authors measured the Mössbauer spectra of both bulk material and extracted metal fraction after magnetic separation (see Figure 23). The bulk spectra of Villalbeto de la Peña L6 and Lavras do Sul L5 consist of four components with two magnetic sextets and two quadrupole doublets.…”
Section: Ordinary Chondritesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies of equilibrated L ordinary chondrites Villalbeto de la Peña L6 and Lavras do Sul L5 [88,89], the authors measured the Mössbauer spectra of both bulk material and extracted metal fraction after magnetic separation (see Figure 23). The bulk spectra of Villalbeto de la Peña L6 and Lavras do Sul L5 consist of four components with two magnetic sextets and two quadrupole doublets.…”
Section: Ordinary Chondritesmentioning
confidence: 99%
“…Parameters for the magnetic fraction were: δ = 0.04 mm/s, H eff = 314 kOe, A = 23.5% for taenite (1); δ = 0.02 mm/s, H eff = 337 kOe, A = 76.5% for kamacite (2). The authors of [89] found two sextets assigned to kamacite and tetrataenite in the spectrum of the metal separate from Lavras do Sul L5, as well as revealed an additional singlet peak related to the paramagnetic γ-Fe(Ni, Co) phase (a brief discussion about questionable term "antitaenite" see above in Section 6.1). An unusual result was obtained in the study of Ararki L5 ordinary chondrite in [90].…”
Section: Ordinary Chondritesmentioning
confidence: 99%
“…Thus, following the standard classification 5 6 , this meteorite can be classified as a LL ordinary chondrite.…”
Section: Discussionmentioning
confidence: 99%